Non-destructive measurement of photoexcited carrier transport in graphene with ultrafast grating imaging technique. (October 2016) - Chen, Ke; Yogeesh, Maruthi Nagavalli; Huang, Yuan; Zhang, Shaoqing; He, Feng; Meng, Xianghai; Fang, Shaoyin; Sheehan, Nathanial; Tao, Tiger Hu; Bank, Seth R.; Lin, Jung-Fu; Akinwande, Deji; et al.
Abstract: Graphene has great potential for fabrication of ultrafast opto-electronics, in which relaxation and transport of photoexcited carriers determine device performance. Even though ultrafast carrier relaxation in graphene has been studied vigorously, transport properties of photoexcited carriers in graphene are largely unknown. In this work, we utilize an ultrafast grating imaging technique to measure lifetime ( τ r ), diffusion coefficient ( D ), diffusion length ( L ) and mobility ( μ ) of photoexcited carriers in mono- and multi-layer graphene non-invasively. In monolayer graphene, D ∼10, 000 cm 2 /s and μ ∼120, 000 cm 2 /V have been observed, both of which decrease drastically in multilayer graphene, indicating that the remarkable transport properties in monolayer graphene originate from its unique Dirac-Cone energy structure. Mobilities of photoexcited carriers measured here are several times larger than the Hall and Field-Effect mobilities reported in literature (<15, 000 cm 2 /V), due to the high energy of photoexcited carriers. Our results indicate the importance of obtaining monolayer graphene to realize high-performance graphene devices, as well as the necessity to use transport properties of photoexcited carriers for predicting the performance of graphene-based opto-electronics.